Penerapan Prinsip Ergonomi Untuk Meningkatkan Produktivitas di SMK PAB 8 Sampali - Fragastia, Vidi Agung; Siregar, Alam Taufik (LPPM Universitas Potensi Utama, 2023)
This community service aims to apply ergonomic principles to increase productivity at PAB 8 Sampali Vocational High School (SMK). Ergonomics is the main focus because of its vital role in creating a comfortable and efficient work environment. This service approach uses participatory methods involving teaching staff, students and other related parties. Various activities were carried out, ranging from evaluating the condition of classrooms and furniture to providing education on ergonomic work patterns. The results of the service show increased awareness of the importance of ergonomics in the school environment as well as the implementation of practices that improve working conditions. It is hoped that this service will not only provide direct benefits for SMK PAB 8 Sampali, but will also become an example for other educational institutions in increasing productivity through the application of ergonomic principles. Through strong collaboration between teachers, students and related parties, it is hoped that this service can have a sustainable impact in improving welfare and achievement in the school environment.